Penerapan Pemberian Hak Asuh Anak Belum Mumayyiz kepada Ayah dalam (Studi Kasus Perkara Nomor 2887/Pdt.G/2017/Pa Js) - Asima Naslah; Rohmad Adi Yulianto; Moh Zakky (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2021)
This study entitled the application of mumayyiz (maintaining and educating children to adults or able to stand alone) child custody rights to fathers. The formulation of the problem in this study are: (1) How is the arrangement of custody of children to children not yet mumayyiz in the Islamic Law Compilation? (2) Does the Compilation of Islamic Law also regulate the granting of unmumayyiz child custody to the father after the divorce? (3) How is the application of the provision of child custody rights to the father in case Number 2887 / Pdt.G / 2017 / PA JS? This research method is Normative Law. legal research is a method that examines document studies, namely using various data such as court decisions, legal theory, legislation and the opinions of scholars in the research location. Data were analyzed using descriptive analysis method. The results of the study show that the regulation and legal basis regarding granting custody of children is not yet mumayyiz to the father which is a marriage bond between a man and a woman, but on the way to fostering a household it has broken based on the Court's decision in 2015, from the divorce has given birth. two children who are not yet mumayyiz. The occurrence of a lawsuit for child custody has not yet been filed with the Court. Where the main point of the dispute between the Plaintiff and Defendant is regarding child custody based on the provisions of Article 49 paragraph (2) number 11 of Law Number 7 of 1989, as amended by Law Number 3 of 2006 and Law Number 50 Years 2009 jo. Article 156 letter e Compilation of Islamic Law, this case is the absolute competence of the religious court. Previously the Panel of Judges had attempted to reconcile the Plaintiff and Defendant, as well as the mediation process was carried out, but it was unsuccessful, and the parties had two witnesses who gave testimony during the process. the trial which has a proof value is independent (vrij bewijs kracht). From the hadil of the research, the stages of handling cases of child custody have not been mumayyiz which decided that the child custody falls to the father to guarantee a sense of security, peace.